Between Partnership and Opposition: The Role of Environmental NGOs in Regional Policy Dynamics in Lampung Province - Mukhlis, Maulana; Yulianto, Yulianto; Umayasari, Ulfa (Journal Public Policy, 2025)
This study explores the dynamic and multifaceted roles of environmental non-governmental organizations (NGOs)—WALHI, Watala, and Mitra Bentala—in shaping regional environmental policy in Lampung Province, Indonesia. It aims to analyze how these NGOs navigate between collaboration and opposition in their interactions with the government, while addressing environmental challenges. Using a descriptive qualitative method, data were collected through interviews with NGO representatives, government officials, and environmental policy observers using a snowball sampling technique, complemented by relevant secondary data. The findings reveal that the three NGOs actively engage in environmental advocacy through campaigns, research, and grassroots mobilization. Their roles extend from being policy partners to critical watchdogs, depending on the alignment between government actions and environmental goals. Despite their significant influence, these NGOs face structural challenges, including limited resources and political resistance. The study underscores the constructive nature of the tension between NGOs and the government, where conflict serves as a form of policy oversight. Furthermore, NGO-facilitated community participation enhances the responsiveness of environmental policy to local needs. While the study is limited in scope, it contributes to the broader discourse on civil society's role in policy-making and suggests pathways to strengthen NGO-government collaboration for more inclusive and sustainable environmental governance at the regional level.